Exploration of Digital Transformation Technologies in South Korea through Startup and Scale-up Ecosystem Analysis - Changjun Lee (International Telecommunications Society (ITS), 2024)
This study delves into the contemporary phenomenon of the convergence of digital technology and the service industry, aiming to provide a profound analysis and propose future-oriented directions for industrial development. It seeks to offer academic insights and practical guidelines through this exploration. The necessity of the research stems from the significant impact of digital technology in today's society, which is reshaping traditional service industry landscapes and prompting innovations in service delivery. Understanding these technological shifts is crucial for formulating effective industrial strategies and policies. This era of Digital Transformation (DT) reflects a transition from vertically integrated firms to disaggregated supply chains, highlighting the evolution of business competition into a fusion on digital platforms. The research aims to develop a new analytical framework to view the digital transformation process in the service industry, thereby innovating research and practical approaches in this field. A focus on innovative startups driving digital transformation is employed, with in-depth analyses using topic modeling and network analysis to understand their impact on the service industry. The study also investigates the fusion and trends within the service industry, utilizing topic modeling to examine classification methods and analyze the convergence trends of technology and business models (BM). Furthermore, the research aims to clarify the employment impacts within the digital transformation ecosystem. By analyzing factors influencing employment changes, it intends to provide insights into future employment trends and policy directions, preparing for the forthcoming era of advancements like artificial intelligence. This comprehensive approach not only aims to understand the current changes systematically but also to prepare for the rapidly evolving digital era's demands on the service industry.
Keywords: 330